Cost effectiveness of detecting Barrett's cancer. Issue 4 (October 1996) - Wright, T A; Gray, M R; Morris, A I; Gilmore, I T; Ellis, A; Smart, H L; Myskow, M; Nash, J; Donnelly, R J; Kingsnorth, A N
Abstract : BACKGROUND: Screening Barrett's oesophagus is controversial owing to a large variation in the reported incidence of neoplastic change and lack of evidence that screening improves tumour prognosis. AIMS: To determine the incidence of Barrett's cancer, its cost of detection, and stage of disease at time of diagnosis. PATIENTS AND METHODS: Data from our surveillance programme have been reviewed to assess the incidence of malignant change, tumour stage at diagnosis, and the cost per cancer detected. RESULTS: 166 patients had annual endoscopic surveillance. Six patients (five men) developed cancer-an incidence of one cancer per 59 male and 167 female patient-years of follow up. The screened group had a significantly earlier stage than a control group of unscreened cancers (p < 0.05). The cost of detecting one cancer was Pounds 14 868 for men and Pounds 42 084 for women. CONCLUSIONS: The cost of screening for Barrett's cancer is high but may be justified on the basis of the high incidence of detecting early stage disease.